Relationships Self-Regulation Learning and Academic Stress First Year Students at Faculty of Nursing University of Jember - Rista Dwi Pratiwi; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Nursing and Health Sciences Journal (NHSJ), 2021)
The increase self-regulation learning has an important role related to academic stress management. First-year students are faced with various academic rules and demands that cause first year students to be stressed. This research analyze the correlation between self-regulation learning and academic stress of first-year students of the Faculty of Nursing, University of Jember. This research method is a cross-sectional study of 126 first-year students using cluster random sampling techniques. Bivariate analysis using Kendall tau b correlation (α <0.05 CI = 95%). The research instruments used were Self-Regulated Learning (Cronbach Alpha = 0.864) and Educational Stress Scale for Adolescents (Cronbach Alpha = 0.849). The result of Kendall tau b correlation test results show p-value 0.015 (α < 0.05) and t = - 0.150. This study found that self-regulation learning correlated to academic stress first-year students of the Faculty of Nursing, University of Jember. The correlation results showed a negative relationship direction with very weak strength, the higher self-regulation learning, the lower level of perceived academic stress. From the results and conclusions, researcher hopes that of first-year nursing faculty students can make more efforts to improve self-regulation learning process as an effort to deal with various problems during the lecture period.